Encountering the shoreline: ecology and infrastructure on the early modern Newfoundland coast. Issue 4 (2nd October 2022) - Nguyen, Jason
Abstract: This article looks at the colonial fishing villages and maritime infrastructure along the early modern Newfoundland shoreline. It argues that, during the seventeenth and eighteenth centuries, the establishment of settlements and the construction of seagoing vessels, preservation stations, and other logistical sites at and across the littoral line supported the commercialization of the global cod market while fundamentally altering the coastal ecologies of the North Atlantic waters. The Grand Banks of Newfoundland, the underwater plateaus that provided shallow feeding conditions for underwater life, made the sea shelf one of the richest fishing regions in the world. On a global scale, the commercial extraction and preservation of cod supported the expanding diet and political economy of the early modern imperial state. On a local scale, the construction of buildings along the shoreline intruded on the littoral ecosystem and impelled the relocation of the native Beothuk inhabitants to the island's interior, thereby highlighting the genocidal ramifications of European coastal development. How, this article asks, might one conceptualize the logistical architecture of the Newfoundland fisheries as both a spatial node within a global network of trade as well as a material intrusion into the ecology of the North Atlantic coastline?